Energy Efficiency of a Building Using Capacitors Optimization - Amirul Asyraf Mohd Kamaruzaman; Muhammad Murtadha Othman; Aainaa Mohd Arriffin; Ismail Musirin; Muhd Azri Abdul Razak; Zilaila Zakaria (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper presents the optimal location and sizing of capacitors to reduce the total power losses as well as its investment cost for a distribution system in a building. The capacitors location and sizing will be randomly chosen repetitively, via Stochasitic optimization method using MATLAB® and SIMULINK® software. The optimal capacitors location and sizing will be picked via analysis and comparisons between the results. The result shows improvement in power losses with minimal investment cost whilst providing optimal sizing and location of capacitors to be installed in a building.